2010
DOI: 10.1080/10824669.2010.495687
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Reading Achievement and Countering the “Fourth-Grade Slump”: The Impact of Direct Instruction on Reading Achievement in Fifth Grade

Abstract: Previous research has documented a substantial decline of standardized test scores of children from low-income backgrounds, relative to more advantaged peers, in later elementary grades, the so-called ''fourth-grade slump.'' This article examines changes in reading achievement from first to fifth grade for students in a large urban school system with a high proportion of students from economically deprived backgrounds. Students received first-grade reading instruction from Direct Instruction (DI), Open Court, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…For example, stronger effects were expected when students had greater exposure to the material (e.g., starting in kindergarten, longer periods of intervention, and greater daily exposure) and when teachers had been well trained (Carlson & Francis, 2002;MacIver & Kemper, 2002;O'Brien & Ware, 2002;Stockard, 2011;Vitale & Joseph, 2008). Previous research also suggested that positive effects would be maintained after discontinuation of intervention (Becker & Gersten, 1982;Meyer, 1984;Stockard, 2010). However, it could be reasonable to expect that the maintenance effects would be smaller than those from immediate postintervention and that the impact of the programs could decline as the maintenance period lengthened.…”
Section: The Current Reviewmentioning
confidence: 99%
“…For example, stronger effects were expected when students had greater exposure to the material (e.g., starting in kindergarten, longer periods of intervention, and greater daily exposure) and when teachers had been well trained (Carlson & Francis, 2002;MacIver & Kemper, 2002;O'Brien & Ware, 2002;Stockard, 2011;Vitale & Joseph, 2008). Previous research also suggested that positive effects would be maintained after discontinuation of intervention (Becker & Gersten, 1982;Meyer, 1984;Stockard, 2010). However, it could be reasonable to expect that the maintenance effects would be smaller than those from immediate postintervention and that the impact of the programs could decline as the maintenance period lengthened.…”
Section: The Current Reviewmentioning
confidence: 99%
“…Explicit and clear explanations as part of direct instruction cause learners to recognize problem structure and interpret data efficiently (Kirschner et al, 2006). Through this, direct instruction has been linked to successful learning in general and practical problem-solving specifically (Stockard, 2010;Stockard et al, 2018).…”
Section: The Benefits Of Example-free Explanationsmentioning
confidence: 99%
“…Tomando en cuenta la segunda variable, procedencia socioeconómica, se encuentran algunas investigaciones que compararon métodos de adquisición de la lectura y escritura y concluyeron que una enseñanza más sistemática de las correspondencias grafema-fonema arrojaba mejores resultados que métodos más globales y que su efecto era mayor en nivel socioeconómico bajo que medio (BRADY, 2011), o que los efectos positivos de los métodos centrados en el significado son menos frecuentes con los estudiantes con dificultades y entre los estudiantes de los sectores de bajos recursos (STAHL;MILLER, 1989). Stockard (2010) realizó un seguimiento del nivel lector de estudiantes desde 1er. a 5to grado procedentes de escuelas que atendían a grupos económicamente desfavorecidos.…”
Section: Pero ¿Y El Aprendizaje?unclassified